2021
DOI: 10.3390/ma14051255
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Epoxy Resin Polymer as Self-Healing Cementitious Materials Agent in Mortar

Abstract: This research investigated the application of epoxy resin polymer as a self-healing strategy for improving the mechanical and durability properties of cement-based mortar. The epoxy resin was added to the concrete mix at various levels (5, 10, 15, and 20% of cement weight), and the effectiveness of healing was evaluated by microstructural analysis, compressive strength, and non-destructive (ultrasonic pulse velocity) tests. Dry and wet-dry conditions were considered for curing, and for generating artificial cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Hydrogel particles facilitate the self-healing process in concrete by utilizing their stored water to stimulate the hydration of cement, thereby mitigating the self-shrinkage of the mixture [37]. Huseien et al [38] added epoxy resins of different mass fractions to concrete and evaluated them comparatively via both microscopic observation and macroscopic tests; they found that specimens prepared with epoxy resins containing 10% by weight of cement had improved mechanical properties after curing. The healing efficiency achieved was 71.8%.…”
Section: Autogenous Healingmentioning
confidence: 99%
“…Hydrogel particles facilitate the self-healing process in concrete by utilizing their stored water to stimulate the hydration of cement, thereby mitigating the self-shrinkage of the mixture [37]. Huseien et al [38] added epoxy resins of different mass fractions to concrete and evaluated them comparatively via both microscopic observation and macroscopic tests; they found that specimens prepared with epoxy resins containing 10% by weight of cement had improved mechanical properties after curing. The healing efficiency achieved was 71.8%.…”
Section: Autogenous Healingmentioning
confidence: 99%
“…The cracks formed in the close proximity were also self-repaired and polymerized as the embedded catalyst acted with the healing agent. Figure 7b shows a standard broken microcapsule [127]. Quicker detection and reactions to a crack in the concrete matrix plus the ability to self-heal more kinds of cracks demonstrated the proficient autonomous healing of the encapsulation method [128].…”
Section: Self-healing Approachmentioning
confidence: 99%
“…In this case, it is relatively easy to design additional protection against elevated temperature, e.g., from board materials (Figure 3) [17]. An additional possible application of epoxy resins in concrete structures could be in the reparation of damaged concrete structures [18], the modification of concrete surfaces, and the elimination of cracks on concrete surfaces [19]. The other possibility of using synthetic resins is in the improvement of mortar-based building materials [20].…”
Section: Introductionmentioning
confidence: 99%